Optimus Primed: Media Cultivation of Robot Mental Models and Social Judgments - Banks, Jaime (Frontiers in Robotics and AI, 2020)
Media influence people’s perceptions of reality broadly and of technology in particular. Robot villains and heroes—from Ultron to Wall-E—have been shown to serve a specific cultivation function, shaping people’s perceptions of those embodied social technologies, especially when individuals do not have direct experience with them. To date, however, little is understood about the nature of the conceptions people hold for what robots are, how they work, and how they may function in society—as well as the media antecedents and relational effects of those structures. This study takes a step toward bridging that gap by exploring relationships among individuals’ recall of robot characters from popular media, their mental models for actual robots, and social evaluations of an actual robot. Findings indicate that mental models consist of a small set of common and tightly linked components (beyond which there is a good deal of individual difference), but robot character recall and evaluation have little association with whether people hold any of those components. Instead, data are interpreted to suggest that cumulative sympathetic evaluations of robot media characters may form heuristics that are primed by and engaged in social evaluations of actual robots, while technical content in mental models is associated with a more utilitarian approach to actual robots.